La gestión directiva en el clima organizacional, en la unidad educativa Luis Rivadeneira, parroquia río verde, cantón santo domingo. Manual de estrategias para mejorar el clima organizacional de la comunidad educativa. - Andino Silva, Margoth Rosario (2016)
The present research is based with the topic “Organizational environment Luis Rivadeneira Educative Unit, Río Verde Parish, Santo Domingo Canton. A manual to improve the organizational climate of the educational community” where this research is applied, it has a population of 540 students, 27 teachers and 3 administrative people, research and development applied to the sample given population for effect. It was detailed the characterization of the target, foundation, as well as the theoretical basis of the research variables. Also was established methodology that containing form, paradigm, scope and levels of investigation, also the operationalization variables of the dependent and independent, in addition to the methods, techniques and procedures of research variables, as well as population and sample collection process and information analysis. The research results containing the analysis and interpretation of results, the testing of hypotheses, in addition to the conclusions and recommendations, and finally. The proposal that containing: the subject, the data information, justification, objectives, feasibility analysis, operating a model and an action plan. The strategies paper to improve the organizational environment of the school community, as an instrument to guide the management board, of providing a focus on quality education, executive management, but primarily provides a guidance on which to base the work institutional managers to consolidate the organizational climate of the corresponding educational community.